2023
DOI: 10.1109/temc.2023.3262322
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Exposure to Electromagnetic Fields From User Equipment Antennas Above 100 GHz

Abstract: The next-generation mobile communication technology may exploit the higher frequency spectrum beyond 100 GHz, while most studies on electromagnetic field (EMF) exposure from mobile communication devices focus on frequencies below 100 GHz. In this paper, the EMF exposure from sub-terahertz antennas designed for future mobile communication is evaluated with a multilayer flat tissue phantom. It is demonstrated that the deposited EMFs can be evaluated by neglecting the deep tissue in the simplified phantom. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…It was found that the normal incidence is the worst-case for surface temperature rise when bare skin is directly illuminated as it corresponds to the maximum APD for a given incident power density (IPD). Several groups computed APD and resultant temperature rise above 6 GHz using various skin models, exposure conditions and numerical methods [14], [15], [16], [17], [18], [19], [20], [21]. These computational results indicate that an APD ranging from 34-60 W/m 2 is required to elevate the temperature of bare skin by 1 • C.…”
mentioning
confidence: 99%
“…It was found that the normal incidence is the worst-case for surface temperature rise when bare skin is directly illuminated as it corresponds to the maximum APD for a given incident power density (IPD). Several groups computed APD and resultant temperature rise above 6 GHz using various skin models, exposure conditions and numerical methods [14], [15], [16], [17], [18], [19], [20], [21]. These computational results indicate that an APD ranging from 34-60 W/m 2 is required to elevate the temperature of bare skin by 1 • C.…”
mentioning
confidence: 99%